How not to manage a pandemic, and how to recover from it: Lessons from Ecuador - Marco Coral-Almeida; Sarah J. Carrington; Vanessa D. Carrión-Yaguana; Guido Mascialino (FACETS, 2022)
Since the initial outbreak in December 2019, the COVID-19 pandemic has resulted in more than four million deaths worldwide. Ecuador initially experienced one of the worst coronavirus outbreaks in the world. The pandemic quickly overwhelmed health care systems resulting in excess deaths of 37 000 from March to October, 2020. The public health measures taken to stop the spread of the virus had a devastating impact on the economy. There was a sharp contraction (7.8%) in Ecuador’s GDP in 2020. Furthermore, income poverty and inequality increased dramatically. The lasting effects of the pandemic will be harder to overcome. This article recounts and analyzes the COVID-19 pandemic in Ecuador, to draw lessons from this complex experience, and from the benefit of limited but important successes. We also aim to provide suggestions for best practices moving forward.